TINJAUAN PELAKSANAAN UJIAN NASIONAL DARI SISTEM PENGENDALIAN INTERNAL - FIRMANSYAH, ANDI (Jurnal Akuntansi AKUNESA, 2014)
This paper discusses the implementation of the Ujian Nasional (UN) in terms of internal control. Reviewing the implementation of the UN 2013 from the achievement of the purposes of the application of control systems because the UN in 2013 has gotten a bad image on the implementation. Also examines the efforts of the government in making changes in implementation of the UN Model 2014, an effort to improve the quality of national education. This paper written based on the review of documents and literature related to control systems and procedures for implementation of UN   Keywords: UN, review, internal control systems